2016
DOI: 10.1128/iai.00164-16
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Clearance of Pseudomonas aeruginosa by Peroxisome Proliferator-Activated Receptor Gamma

Abstract: fThe pathogenic profile of Pseudomonas aeruginosa is related to its ability to secrete a variety of virulence factors. Quorum sensing (QS) is a mechanism wherein small diffusible molecules, specifically acyl-homoserine lactones, are produced by P. aeruginosa to promote virulence. We show here that macrophage clearance of P. aeruginosa (PAO1) is enhanced by activation of the nuclear hormone receptor peroxisome proliferator-activated receptor gamma (PPAR␥). Macrophages treated with a PPAR␥ agonist (pioglitazone)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…QS molecules have multiple effects on host cells, including disruption of transcriptional signaling mechanisms, to enable establishment of infection. Recently, we have shown that PAO1 and 3O‐C12‐HSL attenuate PPARγ expression in macrophages and lungs of mice that were infected with PAO1 (20). We and others have shown that airway epithelium is critical in mounting host response to P. aeruginosa lung infection (2226); therefore, we investigated the direct impact of QS gene–expressing PAO1 and 3O‐C12‐HSL on PPARγ levels on airway epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…QS molecules have multiple effects on host cells, including disruption of transcriptional signaling mechanisms, to enable establishment of infection. Recently, we have shown that PAO1 and 3O‐C12‐HSL attenuate PPARγ expression in macrophages and lungs of mice that were infected with PAO1 (20). We and others have shown that airway epithelium is critical in mounting host response to P. aeruginosa lung infection (2226); therefore, we investigated the direct impact of QS gene–expressing PAO1 and 3O‐C12‐HSL on PPARγ levels on airway epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest an immunomodulatory role for PPARγ in host response to infection in experimental systems (49, 50). We have recently shown that PPARγ ligands induce PON‐2 and enhance the clearance of P. aeruginosa in macrophages (20). As PPARγ induces PON‐2, which can hydrolyze QS molecules, we hypothesized that PPARγ activation may attenuate biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Singh et al speculated that the discrepancy between their results and those reported in the meta-analysis might be explained by different detection biases. In Gram-negative bacterial infections, PPARγ activation increased bacterial killing of pseudomonads, 38,39 and pretreatment with partial-or selective-PPAR-γ agonists ameliorated a pathological change in Escherichia coli meningitis by suppressing interleukin 6 production in the brain. However, the observational studies were prone to unmeasured residual confounding and the "healthy user" effect.…”
Section: Discussionmentioning
confidence: 99%